Neonatal bone mass: influence of parental birthweight, maternal smoking, body composition, and activity during pregnancy. - Godfrey, K; Walker-Bone, K; Robinson, S; Taylor, P; Shore, S; Wheeler, T; Cooper, C (2001)
Evidence is accumulating that intrauterine growth and development may influence an individual's risk of osteoporosis in later adult life. To examine maternal and paternal influences on intrauterine skeletal growth, we used dual-energy X-ray absorptiometry to measure the neonatal bone mineral content (BMC) and bone mineral density (BMD) of 145 infants born at term. Independently of the infant's duration of gestation at birth, the birthweights of both parents and the height of the father were positively correlated with neonatal whole body BMC. Women who smoked during pregnancy had infants with a lower whole body BMC and BMD; overall, there was a 7.1-g (11%) average difference between whole body BMC of infants whose mothers did and did not smoke during pregnancy (p = 0.005). Women with thinner triceps skinfold thicknesses (reflecting lower fat stores) and those who reported a faster walking pace and more frequent vigorous activity in late pregnancy also tended to have infants with a lower BMC and BMD (p values for BMC; 0.02, 0.03, and 0.05, respectively). Maternal thinness and faster walking pace but not maternal smoking or parental birthweight also were associated with lower bone mineral apparent density (BMAD). The influences on skeletal growth and mineralization were independent of placental weight, a marker of the placental capacity to deliver nutrients to the fetus. These observations point to a combination of genetic and intrauterine environmental influences on prenatal skeletal development and suggest that environmental modulation, even at this early stage of life, may reduce the risk of osteoporosis in adulthood.